Periodontal Tissue Engineering After Tooth Replantation - da Silva Assuncao, Luciana Reichert; Colenci, Renato [UNESP]; Ferreira do-Amaral, Caril Constante [UNESP]; Sonoda, Celso Koogi [UNESP]; Bomfim, Suely Regina Mogami [UNESP]; Okamoto, Roberta [UNESP]; Golim, Márjorie de Assis [UNESP]; Deffune, Elenice [UNESP]; Percinoto, Célio [UNESP]; Oliveira, Sandra Helena Penha de [UNESP] (Amer Acad Periodontology, 2011)
Background: Blood-derived products, platelet-poor plasma (PPP) and platelet-rich plasma (PRP), constitute an approach in the enhancement of tissue healing. PRP has also been used as a scaffold for bone marrow stem cells in tissue engineering. This study evaluates the effect of PPP, calcium chloride activated PRP (PRP/Ca), calcium chloride and thrombin-activated PRP (PRP/Thr/Ca), and bone marrow mononuclear cells and PRP/Ca (BMMCs/PRP/Ca) on the healing of replanted dog teeth.Methods: After 30 minutes of extraction, teeth were replanted with 1) no material (control); 2) PPP; 3) PRP/Ca; 4) PRP/Thr/Ca; or 5) BMMCs/PRP/Ca. Histologic, histomorphometric, and immunohistochemical analysis was assessed 120 days after replantation. Data from histomorphometric analysis were analyzed statistically (analysis of variance, Tukey; P < 0.05). Quantitative immunohistochemical analysis was analyzed by Kruskal-Wallis and Dunn post hoc test (P < 0.05).Results: Flow cytometry analysis showed 55.98% of CD34(+) and 32.67% of CD90/Thy-1 for BMMCs sample. BMMCs/PRP/Ca presented the largest areas of replacement resorption characterized by osseous ingrowth into cementum (P < 0.05), with intense immunomarcation for tartrate-resistant acid phosphatase. The PRP/Ca group also showed areas of replacement resorption with significant immunomarcation for osteopontin. PRP/Thr/Ca presented no replacement resorption. PPP showed areas of inflammatory resorption, with immunomarcation for tartrate-resistant acid phosphatase.Conclusions: The results suggest that platelets activated with thrombin play an important role in the healing of tissues after tooth replantation. Additional studies are necessary to test other materials, because PRP/Ca did not present an appropriate scaffold for undifferentiated cells in the treatment of avulsed teeth. J Periodontol 2011;82:758-766.
Keywords: Bone marrow; platelet-rich plasma; stem cells; tissue engineering; tooth replantation